Analysis of Cash Flow and Net Income on Stock Prices in Mining Companies in Indonesia - Chindy Anggraeni Luthfihani; Se Tin (International Journal of Entrepreneurship, Business, and Creative Economy, 2024)
Information about a company's cash flow and net income is useful for readers of financial statements, especially investors, as a basis for analysing the company's ability to create profits because investors must see the stock price when making an investment. Based on these considerations, this study aims to examine the effect of cash flow and net income on stock prices in mining companies in Indonesia. The population of this study consisted of 19 companies, and a sample of 36 financial records from three coal mining companies was used using a purposive sampling technique. The author uses a multiple linear regression analysis method. The results showed that net income significantly affects stock prices, while cash flow has no significant effect individually. However, when considered together, both cash flow and net income influence stock prices. This study provides valuable insights for future investors and researchers by recommending sample expansion, a more in-depth literature review, and diverse research methods.